1997
DOI: 10.1111/j.1365-2044.1997.98-az0094a.x
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared spectroscopy changes during hypothermic circulatory arrest with retrograde cerebral perfusion

Abstract: SummaryWe report on the changes in cerebral near-infrared spectroscopy during grafting of a thoraco-abdominal aneurysm. A 58-year-old man presented with a complex dissecting aortic aneurysm. Repair of the aneurysm was performed under hypothermic circulatory arrest with retrograde cerebral perfusion. Cerebral near-infrared spectroscopy monitoring revealed a reduction in the values recorded for total haemoglobin, oxygenated haemoglobin and cytochrome aa3 along with an increase in deoxygenated haemoglobin during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…From these studies [9,79], S j o 2 can be considered as a good monitor for safe management of the cerebrum during aortic arch replacement. In addition, near-infrared spectroscopy has been used to monitor regional cerebral oxygenation in adults undergoing aortic arch surgery [29], and in children undergoing hypothermic circulatory arrest [80].…”
Section: Efficient Brain Cooling and S J Omentioning
confidence: 99%
“…From these studies [9,79], S j o 2 can be considered as a good monitor for safe management of the cerebrum during aortic arch replacement. In addition, near-infrared spectroscopy has been used to monitor regional cerebral oxygenation in adults undergoing aortic arch surgery [29], and in children undergoing hypothermic circulatory arrest [80].…”
Section: Efficient Brain Cooling and S J Omentioning
confidence: 99%
“…The rSO 2 rapidly falls with the start of HCA but using RCP, the fall appears less rapid. 51,52 This is further evidence that RCP is actually perfusing the brain. The normal human brain weighs about 1400 g and contains approximately 75 ml of blood, but only 10-20 ml is arterial.…”
Section: Is There Evidence That Rcp Perfuses the Brain In Humans?mentioning
confidence: 88%
“…There is good evidence that monitoring rSO 2 provides a real‐time continuous assessment of regional oxygenation of a variety of tissue beds. Rigg et al (10) demonstrated changes in regional cerebral oxygenation associated with retrograde cerebral perfusion on cardiopulmonary bypass. Others have shown that changes in rSO 2 track changes in perfusion of the liver, calf muscles during aerobic exercise, gluteal muscle and visceral perfusion during abdominal aortic surgery (11–13).…”
Section: Discussionmentioning
confidence: 99%